Self-Esteem and Attachment as Predictors of Resilience in Early Adults Experiencing Quarter-Life Crisis - Wina Lova Riza; Nuram Mubina; Lania Muharsih; Linda Mora (Edutran of Psychology and Behavior, 2023)
Resilience is the individual's ability to choose to recover from sad and challenging life events by increasing their knowledge to be adaptive and overcome similar adverse situations in the future. In early adulthood, many individuals experience a condition called quarter-life crisis, where they feel a sense of worry caused by uncertainty about their future life. Therefore, resilience is needed to face the existing challenges, in order to be able to adapt and protect individuals from the rigors of stress. Resilience arises as a protective factor that is distinguished internally and externally. Externally, resilience is related to attachment, which is a continuous affective bond characterized by a tendency to seek and maintain closeness to specific figures, especially when under pressure. Therefore, the purpose of this research is to determine the influence of self-esteem and attachment as predictors of resilience in young adults who are experiencing quarter-life crisis simultaneously. The method in this research is quantitative, with a sample of early adults experiencing quarter-life crisis, thus the sampling technique used in this research is incidental sampling. The data collection technique used a questionnaire with a resilience scale, the standardized Rosenberg Self-Esteem Scale (RSES), and the attachment scale using the Experiences in Close Relationship-Revised-General Short Form (ECR-R-GSF) scale, Additionally, the Developmental Crisis Questionnaire (DQC-12) scale was used to measure quarter-life crisis in early adults. The data analysis technique used in this research is multiple regression analysis. From the research results using SPSS version 27, a significant value was obtained for both independent variables of 0.000 < 0.005, therefore Ha is accepted and H0 is rejected, indicating that self-esteem and attachment together are predictors of resilience in early adults experiencing quarter-life crisis.